PENILIKAN KESALAHAN BERBAHASA INDONESIA YANG BAIK DAN BENAR DALAM KONTEKS SOSIAL-MASYARAKAT DI RUANG PUBLIK - Wirahyuni, Kadek (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2019)
This research is a qualitative descriptive study. Data and data sources used in this study are in the form of pictures or photographs in the field. One characteristic of qualitative research is the data collected in the form of words, images, and not numbers. The researcher also uses field notes in the form of observation notes and other sources. The data needed to answer the problems that want to be solved are (1) data on the types of errors in Indonesian that are good and correct in the public space, (2) data regarding social-community responses to errors in Indonesian that are good and correct in public space. Data collection techniques used in this study are observation and documentation. The results of the research obtained are (1) errors in Indonesian that are good and correct in the public space are divided into three parts, namely spelling mistakes, diction, and structure, (2) the most dominant use of Indonesian language is diction errors or word choices, ( 3) errors in public spaces contained in posters or nameplate / institutions / stores, contained in newspapers or mass media, and contained in social media, (3) responses in the social-community environment are indifferent and do not know that there are errors in Indonesian that are good and correct in the public space.